Influence of soil parameters and canopy structure on root growth and distribution - Serra-Stepke, Ignacio M. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.